Claudia Octavia: praise and criticism from a woman - Faversani, Fábio; Miranda Costa, Maria Luísa (Romanitas - Revista de Estudos Grecolatinos, 2024)
Octavia is paradoxically presented by the sources. On the one hand, she is seen as an ideal wife because she is weak and has no relevant political role in the imperial house. On the other hand, being weak, she does not occupy properly the position that should be filled by the emperor’s wife and weakens the imperial house. This article evaluates this paradox and examines whether the sources described Octavia and her acts or that information should be taken as the composition of a portrait that is drawn in interaction with the other members of the imperial household.
Keywords: Octavia; Domus Caesaris; Nero; Agrippina Minor; Roman empress